Perfil do humor de praticantes regulares de esportes de combate - Duarte, Jonatas Deivyson Reis da Silva (2022)
One of the major public health concerns worldwide is the growing rate of psychopathological diseases such as anxiety and depression. We know that physical exercise plays an important role as an adjuvant in the prevention and treatment of these psychopathologies. Objective: To compare the mood of regular jiu-jitsu, kickboxing and non-sports practitioners. Methods: Twenty-six jiu-jitsu practitioners, twenty-four kickboxing practitioners, and twenty-five non-practitioners of sports participated in this study (all adult males). As instruments, the Brunel Mood Scale (BRUMS) questionnaire was used to assess mood (this questionnaire analyzes six mood variables, i.e., tension–anxiety, depression–melancholy, hostility–anger, fatigue–inertia, vigor–activity and confusion– disorientation) and the International Physical Activity Questionnaire (IPAQ) was used to analyze the level of physical activity. Mood dimensions were assessed using the Kolmogorov–Smirnov test, and the unpaired t-test was used to compare the mean values of the groups. To test the hypotheses in relation to the multiple variables, the Pillai, Roy, Wilks and Hotelling–Lawley tests were used. The significance level adopted was p < 0.05. Results: For the jiu-jitsu and kickboxing groups, there was no difference between the averages (p > 0.05) with both being in an excellent mood. When comparing the group of practitioners of sports with the group of non-practitioners, all negative variables (tension– anxiety, depression–dejection, hostility–anger, fatigue–inertia, and confusion–perplexity) obtained higher scores in the non-practitioners of sports group (p < 0.05). Conclusion: People who regularly practice combat sports had better mental health compared to nonpractitioners. We recommend the indication of these sports by psychiatrists, psychologists, and general practitioners to combat and prevent anxiety and depression.